Factors affecting adherence and non-adherence to the treatment regimen of selected sexually-transmitted infections among Men who have Sex with Men (MSM) in selected vities in Metro Manila - Flores, Sarah May C.​; Santiago​, Richelle L.; Tolentino​, Anne Nicole D. (2017)
Among the different bacteria, viruses, and parasites that are known to be transmitted through sexual contact, three are currently curable with antibiotics: syphilis, gonorrhea, and chlamydia. However, these infections often go undiagnosed and are becoming more difficult to treat with some antibiotics now failing as a result of misuse and overuse. Among the key affected population of this issue are men who have sex with men (MSM) and one of the biggest factors affecting the outcome of a medical treatment and development of resistant strains is patient adherence. This study, a descriptive, cross sectional, and correlational research, focused on the identification of significant factors that affect the adherence and non-adherence to the treatment regimen of selected sexually transmitted infections (STIs) among MSM. A total of 205 participants were recruited in the study where they filled out a self-administered questionnaire that measured their knowledge on STIs (STD-KQ) and assessed their attitude, motivation, and perceptions of their illness, staff, and the clinical setting (PAMPA). The possible barriers to their treatment adherence were also measured using the ASK-20 tool. These factors were analyzed using STATA 13 to determine if they have significant association with treatment adherence and non- adherence which was measured using the MARS-5 scale. The researchers determined that four (4) out of nine (9) factors are predictors of both treatment adherence and non- adherence among MSMs with selected STIs namely, educational attainment (p=0.009), patient knowledge (p=0.008), perception (p<0.001), and barriers (p=0.027). However, the results of this study are subject to recall bias and may be affected by the unequal distribution of population characteristics. Furthermore, the data collection proper was only conducted for seven (7) working days and was facilitated by the staff of social hygiene clinics (SHCs) of the selected cities. It is therefore suggested to further improve the method of conducting the study by extending the data collection period and observing the data collection proper. The study could also be improved by covering other areas or institutions other than SHCs and expanding the coverage of the study to other cities. The improvement of sampling method is also recommended to ensure equal distribution of population characteristics (e.g. age).